Polycrystalline silicon films formation on foreign substrates by a rapid thermal-CVD technique - Slaoui, A.; Monna, R.; Angermeier, D.; Bourdais, S.; Muller, J.C. (Conference Record of the Twenty Sixth IEEE Photovoltaic Specialists Conference - 1997, 1997)
Deposition of polycrystalline silicon films on foreign substrates, such as silicon dioxide, graphite, alumina and mullite, was performed by means of a lamps heating-assisted CVD technique. We employed a cold wall reactor with a high temperature hydrogen reduction of trichlorosilane (SiHCl/sub 3/) as the Si precursor and trichloroborine (BCl/sub 3/) as a dopant source. The effects of operational parameters such as deposition temperature, flow rate, reactant gas, and substrates properties, on the silicon film characteristics (deposition rate, grain sizes and preferred orientations) were extensively investigated. Surface morphology and minority-carrier lifetime of the deposited films were also studied. High deposition rates in the range 1-4 /spl mu/m/min were achieved on all types of substrates. The grains size and preferential orientations were found to be dependent on the deposition parameters as well as on the used substrate.